The Effect of Microcrystalline Cellulose-CaHPO4 Mixtures in Different Volume Ratios on the Compaction and Structural-Mechanical Properties of Tablets - Valentyn Mohylyuk; Artūrs Paulausks; Oskars Radzins; Liga Lauberte (MDPI AG, 2024)
Using microcrystalline cellulose (MCC) with plastic behaviour and calcium phosphate anhydrous (CaHPO4) with brittle behaviour under compaction is very popular in the pharmaceutical industry for achieving desirable structural-mechanical properties of tablet formulations. Thus, mixtures of specific grades of MCC and CaHPO4 were tested in volume proportions of 100-0, 75-25, 50-50, 25-75, and 0-100 at a constant weight-by-weight concentration of sodium stearyl fumarate lubricant, utilizing a state-of-the-art benchtop compaction simulator (STYL'One Nano). Tablet formulations were prepared at 100, 150, 250, 350, 450, and 500 MPa, and characterized by tabletability profile, ejection force profile, proportion-tensile strength relationship, proportion-porosity relationship, pressure-displacement, and elastic recovery profiles, as well as by in-/out-of-die Heckel plots and yield pressures. Interestingly, the 25-75 formulation demonstrated a two-stage out-of-die Heckel plot and was additionally investigated with X-ray micro-computed tomography (µCT). By post-processing the µCT data, the degree of brittle CaHPO4 particles falling apart, along with the increasing compression pressure, was quantified by means of the surface area to volume (S/V) ratio. For the 25-75 formulation, the first stage (up to 150 MPa) and second stage (above the 150 MPa) of the out-of-die Heckel plot could be attributed to predominant MCC and CaHPO4 deformation, respectively.